Factors Affecting Community Participation in the Use of Health Services in Primary Care - Oktapianti, Wanda Aulia; Tanjung, Nadya Ulfa; Hasibuan, Rapotan (Transpublika Publisher, 2025)
The main problem in this study is the low participation of the community in utilizing health services at the Bandar Baru Health Center, Deli Serdang Regency, even though facilities and programs are available. Barriers such as difficult access to transportation, low ownership of health insurance, and inappropriate perceptions of the disease are the main inhibiting factors. The purpose of this research is to examine the various factors that impact the involvement of the community in utilizing health services at the health center. Utilizing a quantitative approach with a cross-sectional framework, the study gathered a sample of 96 participants using accidental sampling methods. The collected data underwent analysis through the chi-square test to determine the association between independent and dependent variables. The findings indicated a notable correlation between accessibility (p=0.001), ownership of health insurance (p=0.031), and perception of diseases (p=0.014) with the utilization of health services. Conversely, factors such as age, gender, education, occupation, and the presence of health professionals did not display a significant relationship (p>0.05). The implications of this study indicate the importance of community-based interventions to improve physical and financial access to health services and public health education. These interventions need to involve cross-sectors and consider local cultural factors so that the use of health services becomes more equitable and sustainable.